Огляд науково-теоретичних аспектів безпеки об'єктів критичної інфраструктури транспорту - Хрутьба, Вікторія Олександрівна; Зюзюн, Вадим Ігорович; Неведров, Дмитро Сергійович (НТУ "ХПІ", 2019)
Проведено аналіз основних науково-теоретичних аспектів, досвіду та концепцій захисту критичної інфраструктури в Україні та світі. Визначено, що на сьогодні важливим та пріоритетним вектором безпекової політики держави є підвищення безпеки та стійкості національної критичної інфраструктури, до якої відносять енергетичні магістральні мережі, нафто- та газопроводи, морські порти, канали швидкісного та урядового зв'язку, системи життєзабезпечення (водо- та теплопостачання) мегаполісів, утилізації відходів, служби екстреної допомоги населенню та служби реагування на надзвичайні ситуації, високотехнологічні підприємства та підприємства військово-промислового комплексу, а також органи центральної влади. Особливе місце серед головних об'єктів критичної інфраструктури України, належить критичним об'єктам транспорту. Ефективне управління важливими складовими критичної інфраструктури, такими як енергетика, промисловість та сфера життєзабезпечення населення вимагає ефективного механізму функціонування сфери безпеки даних об'єктів. Проведена детальна класифікація об'єктів транспортної інфраструктури за вразливістю, яка дозволяє виділити ті з них, які потребують найбільшого захисту. Досліджено місце об'єктів транспорту в загальній системі критичної інфраструктури держави.

The analysis of the main scientific and theoretical aspects, experience and concepts of critical infrastructure protection in Ukraine and the world was carried out. An important and priority vector of the country’s security policy is to increase the security and stability of the national critical infrastructure. Power stations, oil and gas pipelines, seaports, high-speed and public communications channels, cities for life support (water supply and drainage), waste disposal, ambulance services and emergency services, high-tech enterprises and enterprises of the military-industrial complex as well as central authorities are objects of critical infrastructure. Objects of critical infrastructure оf transport are important objects of critical infrastructure in the Ukraine. The objects of transport infrastructure are traffic highways, transport enterprises of state importance, bridges, seaports, airports, pipelines and others. Effective management of critical infrastructure components such as energy, industry and the life-support of the population requires an effective mechanism for the operation of the security of data objects. Detailed classification of transport infrastructure objects has been carried out. These objects are strategic and require special protection. The place of transport objects in the overall system of critical infrastructure of the state is investigated. The analysis of literary sources testifies to the availability of various scientific and theoretical approaches to the security aspects of objects of critical transport infrastructure. In Ukraine there is no mechanism for preventing possible hazardous situations related to the functioning of critical infrastructure.
Reiew of scientific and theoretical aspects of safety of objects of critical infrastructure of transport
Keywords: ризик; захист; транспорт; управління; risk; protection; security